2018
DOI: 10.2217/nnm-2017-0387
|View full text |Cite
|
Sign up to set email alerts
|

Dose-, Treatment- and Time-Dependent Toxicity of Superparamagnetic Iron Oxide Nanoparticles on Primary Rat Hepatocytes

Abstract: A combination of various biomarkers should be employed for the evaluation of the effect of superparamagnetic iron oxide nanoparticles on liver, and each biomarker should be analyzed in a time- and exposure-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 82 publications
1
19
0
Order By: Relevance
“…The exposure of hepatocytes to 50 ppm of P25 and anatase resulted in relatively highest ROS production while exposure to the same concentration of rutile demonstrated lesser ROS production.30TiO 2 Pure rutile50TiO 2 Pure anatase50SPION10Primary rat hepatocytes0–400 μg/mL48 hrsThe LD50 values were calculated as 328.51 ± 18.25 and 319.79 ± 25.73 for one-shot and cumulative treatment styles, respectively. The time-dependent ROS production data from the current study illustrates that ROS can be used as an early and potent diagnostic marker for SPION-induced toxicity as well as other nanotoxicological inquiries in the liver.76Fe 3 O 4 -TiO 2 20–25HL-7702Ti: 0; 6.25; 15.625 25 µg/cm 2 12 hrsFe 3 O 4 -TiO 2 NPs induced cellular ROS generation, reduced cell viability, and induced apoptosis in a dose-dependent manner in HL7702 cells. Mitochondrial membrane was damaged and cytochrome c was released, followed by regulation of apoptosis-related proteins.96 Abbreviations: HSCs, hepatic stellate cells; MMP, matrix metalloprotein; IC50, half-maximal inhibitory concentration; PVA, Polyvinyl alcohol; GSH, glutathione; NLRP3:NLRs, pyrin domain containing 3; LC50, median lethal concentration; MAPK, mitogen-activated protein kinase; AKT, protein kinase B; CHANG, human Chang liver cells; LD50, median lethal dose; SPION, superparamagnetic iron oxide nanoparticles.…”
Section: The Hepatocytes and Metallic Nanoparticles Toxicitymentioning
confidence: 68%
See 1 more Smart Citation
“…The exposure of hepatocytes to 50 ppm of P25 and anatase resulted in relatively highest ROS production while exposure to the same concentration of rutile demonstrated lesser ROS production.30TiO 2 Pure rutile50TiO 2 Pure anatase50SPION10Primary rat hepatocytes0–400 μg/mL48 hrsThe LD50 values were calculated as 328.51 ± 18.25 and 319.79 ± 25.73 for one-shot and cumulative treatment styles, respectively. The time-dependent ROS production data from the current study illustrates that ROS can be used as an early and potent diagnostic marker for SPION-induced toxicity as well as other nanotoxicological inquiries in the liver.76Fe 3 O 4 -TiO 2 20–25HL-7702Ti: 0; 6.25; 15.625 25 µg/cm 2 12 hrsFe 3 O 4 -TiO 2 NPs induced cellular ROS generation, reduced cell viability, and induced apoptosis in a dose-dependent manner in HL7702 cells. Mitochondrial membrane was damaged and cytochrome c was released, followed by regulation of apoptosis-related proteins.96 Abbreviations: HSCs, hepatic stellate cells; MMP, matrix metalloprotein; IC50, half-maximal inhibitory concentration; PVA, Polyvinyl alcohol; GSH, glutathione; NLRP3:NLRs, pyrin domain containing 3; LC50, median lethal concentration; MAPK, mitogen-activated protein kinase; AKT, protein kinase B; CHANG, human Chang liver cells; LD50, median lethal dose; SPION, superparamagnetic iron oxide nanoparticles.…”
Section: The Hepatocytes and Metallic Nanoparticles Toxicitymentioning
confidence: 68%
“…In vitro studies, Fe 3 O 4 NPs exposure to primary rat hepatocytes showed that the excessive production of ROS was mainly due to the damage of mitochondria by MNPs 7677.…”
Section: Mechanisms Of Hepatotoxicity Induced By Metallic Nanoparticlesmentioning
confidence: 99%
“…Gokduman et al investigated the dose, treatment, and time-dependent toxicity of superparamagnetic Fe 3 O 4 NPs (10 nm, 0–400 μg/mL) on primary rat hepatocytes. The obtained results suggested that the response of ROS increased with increasing concentrations of Fe 3 O 4 NPs [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the findings showed that cells transfected with SPIONs acted similarly to viability, proliferation, and differentiation of ADSC cells and these findings are in agreement with the findings obtained by Ankamwar. 60,61 A stable magnetite colloid prepared by true purification is done by magnetite separation in ultrapure water. This was the protocol used in our study and is in agreement with other studies.…”
Section: Dovepressmentioning
confidence: 99%